How the healthcare-seeking socio-cultural context shapes maternal health clients' mHealth utilisation in a Kenyan context - Cheruto, Sowon Karen (Department of Information Systems, 2021)
Problem Statement: Many developing countries are still grappling with poor health as a result of strained healthcare systems. Top among health inequalities is maternal care with maternal mortality rates being almost 19 times higher in developing countries than in their developed counterparts. mHealth presents the potential for developing countries to overcome some of the traditional healthcare challenges. However, despite the compelling evidence for the potential of maternal mHealth from the plethora of effectiveness studies, why when and how interventions work/do not work in different contexts are not fully understood. Socio-cultural factors are one of the most cited reasons for variance in uptake and utilisation of such technologies. To date, research explaining how socio-cultural factors shape mHealth utilisation is sparse. Purpose of the study: The main objective of the study was to explain how mHealth utilisation behaviour emerges within the healthcare-seeking socio-cultural context. To achieve the objective, the study identified the socio-cultural characteristics of the maternal healthcareseeking context and analysed the user-technology interaction within this context. Research methodology: Building on the foundation that human experiences are best understood in situ, the study adopted explanatory methods guided by an interpretivist paradigm. The study drew upon Activity Theory as a lens to understand the maternal mHealth utilisation phenomenon. Hence, we theorised healthcare-seeking as an activity whose cultural aspects were further understood using Hofstede typology of culture. The study used a Kenyan maternal mHealth intervention to elucidate the phenomenon. We employed semi-structured interviews, focus group discussions, observations, informal discussions, and document review to gather data. The sample was purposively selected and comprised various maternal health stakeholders: maternal health clients, their partners, project implementers and healthcare professionals. Key findings: The results of the study show that the healthcare-seeking socio-cultural context which is characterised by socio-cultural attributes such as high-power distance, high uncertainty avoidance, gendered relations, and collectivism shapes mHealth utilisation behaviour in a dialectical process. This process takes place as maternal health clients shape and are shaped by mHealth within their healthcare-seeking socio-cultural context through a process of internalisation and externalisation. From an internalisation perspective, uncertainties and risks in the maternal healthcare-seeking context resulted in hesitated adoption. Contextual perceptions of usefulness of the intervention resulted in the use of mHealth to substitute other healthcare structures while having different perceptions of the role of mHealth created dissonance among the maternal health clients. With regards to externalisation, maternal health clients adopted legitimisation strategies to reduce uncertainties and to develop trust required for initial and continued use of the intervention. They legitimised both the intervention artifact, and the information. Since the mHealth intervention presented appropriate social cues, being accompanied by the expected health provider's persona, maternal health clients readily humanised the intervention. The contextual social norms around pregnancy also presented a need for the maternal health clients to make their mHealth use an ‘appropriate behaviour' by negotiating use with relevant stakeholders in the context. Finally, in response to mHealth technology paradoxes that challenged the very motive of healthcare-seeking, maternal health clients coped by abandoning mHealth, or otherwise accommodating it. Originality/contribution: This study contributed to knowledge, theory, and practice. First, the study suggests theoretical propositions that explain how mHealth utilisation behaviour emerges. These findings may be useful to similar developing-country contexts. A further contribution to theory emerges from the use of Activity Theory to understand the phenomenon. The study helps to operationalise Activity Theory concepts in Information Systems research. Second, the study provides recommendations to practise with regard to the design and implementation of mHealth interventions. These insights may be useful to mHealth designers and implementers in designing mHealth solutions that are contextually relevant. Here, we propose the consideration of mHealth intervention characteristics that will aid utilisation, involving healthcare professionals and other community stakeholders in mHealth implementation and integrating mHealth into existing healthcare structures.